Anatomical Variations Of Mandibular Canines In A Romanian Population And Relation To Prosthetic Treatment - Oana Cella Andrei; Ruxandra Margarit (Romanian Society of Oral Rehabilitation, 2011)
Objective: The anatomy of mandibular canines is not always as simple as can be expected. Their morphological variations must be taken into account in order to prevent the failure of endodontic treatment. The knowledge of these anatomical variations is essential for proper root canal therapy and consequently for the long term success of subsequent prosthetic treatment. We wanted to reveal the presence of mandibular canines with two roots or two canals in the Romanian patients, roots and canals that if remained undetected can be a cause of tooth extraction and failure of prosthetic treatment. Patients and method: This article presents a study on anatomical variations encountered in the mandibular canines used as abutment teeth for fixed prosthesis or mobile denture. The study was done on a sample population of 282 patients from a private practice in Bucharest. We analyzed retrospectively all the new patients that came into the office during a period of time of 3 years, from 2008-2011, seeking various types of treatment. From them, only 36 needed at least one mandibular canine as an abutment. For data processing were used software packages Epi Info, distributed by the OMS and the Data Analysis module of Microsoft Excel. Registering with Excel data on patients produced the original database from which we extracted the significant aspects of this study. The actual processing was done using the program Epi Info Analysis module specialized in performance graphs, tables and statistical tests, as well as with commands Statistical Functions and Chart by MS Excel program. Results: After implementing this study it was observed that by the number of 59 mandibular canines which required endodontic treatment, a number of 56 (95%) had a usual anatomy, while a total of three (5%) presented anatomical variations. From the total of the canines, 49% were used as abutments for removable partial dentures, 19% were used as abutment for ceramic fused to metal bridges, 15% were covered with crowns and 14% were used as abutments for overdentures with magnets. Only 3% was restored by coronary fillings. Conclusion: The results show that such anatomical variations can also occur in Romanian population as much as described in the international literature and cannot be overlooked in private practice. In Romania there are no currently available studies at the level of the population. This anatomical variation is a major risk for both endodontic and prosthetic treatment failure.